Does Gender Matter? Women Business Angels and the Supply of Entrepreneurial Finance - Harrison, Richard T.; Mason, Colin M. (Entrepreneurship Theory and Practice, 2007)
There is a substantial literature on the relationship between gender and access to finance. However, most studies have been concerned with access to debt finance. More recently, the focus of this research has broadened to examine women and venture capital. This article extends the focus further by examining the role of women in the business angel market, which is more important than the formal venture capital market in terms of both the number of ventures supported and total capital flows. Based on a detailed analysis of business angels in the U.K., the study concludes that women investors who are active in the market differ from their male counterparts in only limited respects. Future research into women business angels, and the possible existence of gender differences, needs to be based on more fully elaborated standpoint epistemologies that focus on the experience of the woman angel investor per se, and center on the examination of the role of homophily, social capital, networking, and competition in investment behavior.